A Chemically Self‐Charging Flexible Solid‐State Zinc‐Ion Battery Based on VO2 Cathode and Polyacrylamide–Chitin Nanofiber Hydrogel Electrolyte. Issue 25 (12th May 2021) - Liu, Chaozheng; Xu, Wangwang; Mei, Changtong; Li, Meichun; Chen, Weimin; Hong, Shu; Kim, Won‐Yeong; Lee, Sang‐young; Wu, Qinglin
Abstract: Conventional self‐charging systems are generally complicated and highly reliant on the availability of energy sources. Herein, a chemically self‐charging, flexible solid‐state zinc ion battery (ssZIB) based on a vanadium dioxide (VO2 ) cathode and a polyacrylamide‐chitin nanofiber (PAM‐ChNF) hydrogel electrolyte is developed. With a power density of 139.0 W kg ‐1, the ssZIBs can deliver a high energy density of 231.9 Wh kg ‐1 . The superior electrochemical performance of the ssZIBs is attributed to the robust tunnel structure of the VO2 cathode and the entangled network of PAM‐ChNF electrolyte, which provide efficient pathways for ion diffusion. Impressively, the designed ssZIBs can be chemically self‐charged by the redox reaction between the cathode and oxygen in ambient conditions. After oxidation for 6 h in air, the ssZIBs manifest a high discharging capacity of 263.9 mAh g ‐1 at 0.2 A g ‐1, showing excellent self‐rechargeability. With the assistance of a small amount of acetic acid added to the hydrogel electrolyte, the galvanostatic discharging and chemical self‐charging cycles can reach 20. More importantly, such ssZIBs are able to operate well at chemical or/and galvanostatic charging hybrid modes, demonstrating superior reusability. This work brings a new prospect for designing flexible chemically self‐charging ssZIBs for portable self‐powered systems. Abstract : The robust tunnel structure of a vanadium dioxide cathode and the network of a polyacrylamide–chitin nanofiber hydrogel electrolyte provide efficient pathways for ion diffusion, lead to superior electrochemical performance for solid‐state zinc‐ion batteries. In addition, the flexible chemically self‐charging ssZIBs demonstrate excellent self‐rechargeability and superior reusability, which provide a facile route for portable self‐powered systems.